Crystal structure of (μ2-1,1′-bis(diphenylphosphino)ferrocene-κ2P,P′)-bis[(Z)N-(3-fluorophenyl)-O-methylthiocarbamato-S]digold(I) chloroform solvate, C50H42Au2F2FeN2O2P2S2, CHCl3 - Yeo, Chien Ing *; Tan, Yee Seng *; Tiekink, Edward R. T. * (De Gruyter Open, 2020)
C51H43Au2Cl3F2FeN2O2P2S2, triclinic, P1̄ (no. 2), a = 8.3276(1) Å, b = 13.1116(1) Å, c = 13.5547(1) Å, α = 110.309(1)°, β = 103.132(1)°, γ = 105.601(1)°, V = 1249.86(2) Å3, Z = 1, Rgt(F) = 0.0153, wRref(F2) = 0.0387, T = 100(2) K.